Antecedents and Outcomes of Hospitality Loyalty: A Meta-Analysis. (May 2016) - Tanford, Sarah
Customer loyalty is vital for hospitality businesses. A large body of literature has accumulated on the topic, requiring integration to form generalizations and to make it accessible to operators. In this research, I provide a conceptual framework for classifying indirect and direct loyalty antecedents and outcomes, and quantifying its components using meta-analysis. I analyze 102 studies that produce 423 effect sizes, which are distilled into a summary effect size for each relationship. The analysis reveals strong relationships between direct loyalty antecedents (satisfaction, emotional commitment, service quality, trust, and switching costs) and overall loyalty. However, the magnitude of effects declines significantly as the outcome moves from attitudinal loyalty to behavioral intentions to behavior. As most of our knowledge about loyalty is based on intention measures, the findings suggest that effects on actual loyalty may be smaller than the research would suggest. Indirect loyalty antecedents include experiential, monetary, and relational attributes. It appears that each of these categories affect loyalty through somewhat different processes, although they all relate to satisfaction. The meta-analysis approach allows operators to glean key findings relevant to their business from a single source. It enables researchers to answer research questions and to summarize relationships from a body of literature that cannot be tested conclusively with a single study.